Modelling of Solar PV Micro-inverter using Maximum Power Point Tracking (MPPT) Methods - Abdullah, Fatin Kamilah (2018)
Solar energy is the popular renewable energy that been used nowadays in Malaysia to generate electricity. A photovoltaic (PV) system needed to harvest this energy and have higher efficiency of the production. Maximum power point tracking (MPPT) concepts usually used to extract the solar power from the PV panels. The installation of the micro-inverter in the grid help to reduce the mismatching conditions due to shadowing effect and panel orientation. The concept of the micro-inverter in PV panel where each of the solar panel have their own inverter that connect to the power grid. The inverter concept will converts the DC voltage from the solar panel to an AC voltage and transfer all the energy into the electrical grid. However, the conversion of the conventional micro-inverter depend on its reliability and efficiency. In the meantime, a lower power loss and low circuit cost must considered. This is because to achieve low cost, low harmonic, low circuit size and perform high efficiency. There are many technique of MPPT, from all the techniques that are already been used in the present day, comparison had been made to find the most efficiency technique. Findings from this project considered more to the power, current, voltage supplied from solar PV to inverter part and the output voltage supply to the grid. The outcome from this project will prove that which MPPT method are best for installation.